Genetic Variations of Gene Associated with Adverse Drug Reactions to Valproic Acid in Korean Epileptic Patients - Ji Hyun Yi; Yang-Je Cho; Won-Joo Kim; Min Goo Lee; Ji Hyun Lee (Genomics & Informatics)
The multidrug resistance protein 2 (MRP2, ABCC2) gene may determine individual susceptibility to adverse drug reactions (ADRs) in the central nervous system (CNS) by limiting brain access of antiepileptic drugs, especially valproic acid (VPA). Our objective was to investigate the effect of ABCC2 polymorphisms on ADRs caused by VPA in Korean epileptic patients. We examined the association of ABCC2 single-nucleotide polymorphisms and haplotype frequencies with VPA related to adverse reactions. In addition, the association of the polymorphisms with the risk of VPA related to adverse reactions was estimated by logistic regression analysis. A total of 41 (24.4%) patients had shown VPA-related adverse reactions in CNS, and the most frequent symptom was tremor (78.0%). The patients with CNS ADRs were more likely to have the G allele (79.3% vs. 62.7%, p = 0.0057) and the GG genotype (61.0% vs. 39.7%, p = 0.019) at the g.-1774delG locus. The frequency of the haplotype containing g.-1774Gdel was significantly lower in the patients with CNS ADRs than without CNS ADRs (15.8% vs. 32.3%, p = 0.0039). Lastly, in the multivariate logistic regression analysis, the presence of the GG genotype at the g.-1774delG locus was identified as a stronger risk factor for VPA related to ADRs (odds ratio, 8.53; 95% confidence interval, 1.04 to 70.17). We demonstrated that ABCC2 polymorphisms may influence VPA-related ADRs. The results above suggest the possible usefulness of ABCC2 gene polymorphisms as a marker for predicting response to VPA-related ADRs.